How social media affects the confidentiality of patients? A review of potential problems and recommendations - Beltrán Aroca, Cristina Mª; Girela López, Eloy (Acta Bioethica, 2017)
Personal health data are considered as sensitive information, so they need a “special protection”. We are in a society where Information and Communications Technology (ICT), especially in relation to social networks, offer many opportunities for the exchange of medical information, serving as support, advice or assistance to colleagues who work in the same field or in any other place around the world. Technological advances in communication challenge the concept of “public” and “private,” in a way that the shared information is almost impossible to remove, and could spread rapidly through social networks. Based on our own experience and the different papers reviewed, we believe it is necessary to train health professionals and especially medical students during their academic education to use these tools properly, especially when posting sensitive data in places of public access, as it may have important consequences for the privacy of individuals, both for patients and for their own life.